PENGARUH TINGKAT PENDAPATAN DAN TINGKAT PENDIDIKAN ORANG TUA SERTA DISIPLIN BELAJAR TERHADAP PRESTASI BELAJAR SISWA SMA NEGERI DI BANGKALAN - Matus, Dwi Aprilia (UNIVERSITAS NEGERI SURABAYA, 2016)
This study aimed to analyze whether there is influence the income level of parents on student achievement SMA in Bangkalan, analyzing whether there is any effect of parental education on student achievement SMA in Bangkalan and analyze whether there is influence the discipline of learning on student achievement SMA in Bangkalan. This study uses a quantitative approach. The population in this study were students of class X social studies in high schools in Bangkalan as many as 394 students. In this study the sampling used is simple random sampling, with a sample of 199 respondents. Technique or method of data collection is questionnaire and documentation. The results of this study indicate that there are significant income level tuaterhadap learning achievement with significant value 0,036<5%, no effect of parental education on learning achievement with significance value of 0.561>5% and there are significant learning discipline on achievement belaja with significance value 0 , 21<5%